Efficient short-time hydrothermal depolymerization of sugarcane bagasse in one-pot for cellulosic ethanol production without solid-liquid separation, water washing, and detoxification. (November 2021) - Zheng, Xiaojie; Xian, Xiaoling; Hu, Lei; Tao, Shunhui; Zhang, Xiaodong; Liu, Yao; Lin, Xiaoqing
Graphical abstract: Highlights: SCB was pretreated using liquid hot water at 210 °C for a short time (0 min). Short-time hydrothermal depolymerization of SCB in one-pot was effective. One pot operation omits solid-liquid separation, water washing, and detoxification. The highest ethanol yield of 257 ± 5.51 mg/g SCB reached by SHF strategy. Abstract: In these studies, a low-cost and energy efficiency production of cellulosic ethanol from sugarcane bagasse (SCB) using one-pot without solid-liquid separation, water washing, and detoxification was performed. Firstly, SCB was pretreated using liquid hot water as the only reagent at 210 °C for a short time (0 min), and the solid liquid ratio (SLR) was 1:20 (w/v). Then, the whole slurry of pretreated SCB was enzymatically hydrolyzed and fermented for cellulosic ethanol in one-pot. The results indicated that the one-pot preparation for ethanol achieved a high total fermentable sugar conversion of 84.52 ± 1.24%, containing 88.61 ± 1.57% of glucose and 78.01 ± 1.63% of xylose. Moreover, the ethanol yield reached 257 ± 5.51 mg/g SCB, which was 77.56 ± 1.64% of the theoretical ethanol conversion from SCB. Importantly, there was no wastewater discharge in the whole process. Overall, the present work provides an economically feasible method for ethanol production.